RISK OF REPEATED THROMBOTIC EVENTS IN PATIENTS SURVIVED ACUTE CORONARY SYNDROME AND HAVING LABORATORY PROVEN RESISTANCE TO ACETYLSALICYLIC ACID - N. F. Puchinyan; N. V. Furman; A. R. Kiselev; Ya. P. Dovgalevsky (Рациональная фармакотерапия в кардиологии)
Aim. To evaluate risk of repeated atherothrombotic events in patients survived acute coronary syndrome (ACS) and having poorly reduced platelet aggregation (proven by optical aggregometry) in response to acetylsalicylic acid (ASA) therapy.Material and methods. 200 patients with ACS (aged 56,6±9,2 y.o.) were included in the study. Platelet functional activity during ASA therapy was evaluated with laser aggregometer. ASA resistance was defined if the summarizing index of platelet aggregation (induced with ADP, 5 mμml/l) was 50% or higher during ASA therapy. Observation period was 18±6 months. Atherothrombotic events (unstable angina, myocardial infarction, stroke, cardiovascular death) were considered.Results. Lack ASA response rate was about 12%. Totally 22 repeated atherothrombotic events were registered: 5,6% among ASA sensitive patients and 50% - among ASA resistant patients. Repeated atherothrombotic events were registered in ASA resistance patients during first 14 days. ASA sensitive patients showed repeated atherothrombotic events in some months after ACS. The relative risk of cardiovascular event in ASA resistance patients was 8,92 (CI 95% 4,39; 17,84 р=0,05).Conclusion. The high level of the induced platelet aggregation (proven by laser aggregometry) points to high risk of repeated atherothrombotic events in patients with ACS.